Professores formadores de professores: a gestão pedagógica da aula - Silva, Marciele Taschetto da (2015)
This study is inserted in the Research Field Training, Knowledge and Professional Development , representing the research context on the training of trainers in the area of Exact Sciences and Earth. This study is linked to the research project entitled "The superior teaching moves: specificities in different areas of knowledge and its influence on educational performance" developed by the Pathways Training Group ( GTFORMA ) . The objective of this study is to investigate the implications of training of trainers of teachers in the field of Exact and Earth Sciences in the pedagogical management of the classroom . We emphasize that educational management is constituted as long as the teacher is committed to its education project , organizing and articulating knowledge necessary to train their students and , consequently , for their own training. Thus, considering the challenges of this process , especially given the reality of the absence of a specific preparation for teaching at university, we are interested in analyzing the impact of teacher training ( bachelors and / or licensed ) operating in major courses, in view their pedagogical management. So the choice for studying the practices of teachers management pertaining to the unity of Natural and Exact Sciences, UFSM was due to the fact that the interviews already conducted by GTFORMA group, realize the need to deepen issues related to their formations and practices in the classroom. Moreover, considering the problem we propose to investigate , the university center , where courses are concentrated in this area , is one of the largest at UFSM , where we find teachers with bachelor s degree teaching in major courses and also has the highest concentration of major courses , which is our interest as study context. The methodological option of research is qualitative narrative nature and in terms of analytical interpretation of the narratives of teachers, chose the discursive textual analysis method. We know that the pedagogical management of the classroom involves all areas of teaching, because it is the generative core of teaching and therefore, despite the many challenges present in everyday life, it is necessary that the teacher assume the coaching role building your project instruction with the basic premise meaningful learning of their students.